Determination and modelling of osmotic coefficients and vapour pressures of binary systems 1-and 2-propanol with C(n)MimNTf(2) ionic liquids (n=2, 3, and 4) at T=323.15 K - Noélia Calvar (2011)
The osmotic and activity coefficients and vapour pressures of binary mixtures containing 1-propanol, or 2-propanol and imidazolium-based ionic liquids with bis(trifluoromethylsulfonyl)imide as anion (1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, C(2)MimNTf(2), 1-methyl-3-propylimidazolium bis(trifluoromethylsulfonyl)imide, C(3)MimNTf(2), and 1-butyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide, C(4)MimNTf(2)) were determined at T=323.15 K using the vapour pressure osmometry technique. The experimental osmotic coefficients were correlated using the extended Pitzer model modified by Archer and the MNRTL model, obtaining standard deviations lower than 0.033 and 0.064, respectively. The mean molal activity coefficients and the excess Gibbs free energy for the mixtures studied were calculated from the parameters of the extended Pitzer model modified by Archer. Besides the effect of the alkyl-chain of the cation, the effect of the anion can be assessed comparing the experimental results with those previously obtained for imidazolium ionic liquids with sulphate anions. (C) 2011 Published by Elsevier Ltd.